Micro-PAD card for measuring total ammonia nitrogen in saliva - Thepchuay, Yanisa (2020)
This work presents a portable microfluidic paper-based analytical device (micro-PAD) card for the quantification of total ammonia nitrogen in human saliva. The amount of total ammonia nitrogen in saliva can be an indicator of the status of the oral microbiome with potential correlation to kidney health problems. The developed micro-PAD card comprises twenty units consisting of three stacked layers of circular discs: the sample layer, paper discs impregnated with sodium hydroxide solution, the PTFE membrane layer, and the detection layer, paper discs impregnated with bromothymol blue. The twenty units were aligned on transparent laminating pouches laminated to form the micro-PAD card (7.5 cm × 10.5 cm). Saliva samples can be directly dispensed onto the micro-PAD card and the detection was achieved by the BTB indicator color change, from yellow to blue, after conversion of ammonium into ammonia and diffusion of the ammonia gas through a hydrophobic layer. The determination of total ammonia nitrogen in saliva using the developed micro-PAD card intended to be very simple method and operated without the need of laboratory equipment. A quantification limit of 11.3 NH4+mg L-1 and linear application range from up to 150 NH4+mg L-1 were obtained making it suitable for the expected concentrations of total ammonia nitrogen in human saliva. It was successfully applied to saliva samples and its validation obtained by comparison against a potentiometric method. The card is stable for at least 1 month making it ideal as a portable device for point-of-care diagnosis.